Evaluasi Postur Pekerja Proyek Menggunakan REBA dan RULA pada ErgoFellow - Nofitasari Damayanti Karini; Fakhril Husain; Grita Supriyanto Dewi; Muhammad Syarqim Mahfudz (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2025)
Construction work involves high physical demands and frequently results in non-ergonomic working postures, particularly during bending, lifting, and repetitive manual activities. Such conditions substantially increase the risk of developing Musculoskeletal Disorders (MSDs), especially when performed for prolonged periods without adequate recovery. This study aims to analyze the working postures of construction workers during wall-building activities using the Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) methods integrated within the ErgoFellow software, and to formulate appropriate ergonomic improvement strategies. Data were collected through direct observation, photographic documentation, short interviews, and worker questionnaires. The analysis indicates that the observed postures were dominated by trunk flexion exceeding 60°, neck flexion above 20°, shoulder elevation, wrist deviation, and unstable lower-limb support. The RULA score of 7 places the activity in the “very high risk” category, requiring immediate corrective action. Furthermore, the REBA score of 11 indicates a very high whole-body risk level, signifying the urgent need for ergonomic intervention. The primary contributing factors include non-neutral postures, repetitive motions, external loads of 3–7 kg, and workstation design that does not match workers’ anthropometric characteristics. Based on these findings, recommended improvements include adjusting the height of the mortar container, using long-handled tools, redesigning the workstation layout, and providing training on proper working postures. Implementing these interventions is expected to reduce MSD risks and enhance overall safety in construction activities.